2017
DOI: 10.3748/wjg.v23.i22.4072
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of combined directly acting antivirals for treatment of Chinese chronic hepatitis C patients in a real-world setting

Abstract: AIMTo assess the efficacy and safety of combined directly acting antivirals (DAAs) for the treatment of Chinese chronic hepatitis C (CHC) patients in a real-world setting.METHODSHospitalized CHC patients who were treated with DAAs at Peking University First Hospital between January 2015 and December 2016 were enrolled. Samples and clinical data were collected at 0 wk, 2 wk, 4 wk, 8 wk, 12 wk, or 24 wk during DAAs treatment and at 4 wk, 12 wk, and 24 wk after the end of treatment.RESULTSFifty-four patients who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 38 publications
0
6
0
2
Order By: Relevance
“…An animal study demonstrated that SUA levels may decrease after DAA treatment . Nevertheless, it has been suggested that SUA levels may increase via the performance of human studies . It should be noted that the sample sizes in the previous studies were small.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…An animal study demonstrated that SUA levels may decrease after DAA treatment . Nevertheless, it has been suggested that SUA levels may increase via the performance of human studies . It should be noted that the sample sizes in the previous studies were small.…”
Section: Discussionmentioning
confidence: 94%
“…29 Nevertheless, it has been suggested that SUA levels may increase via the performance of human studies. 30,31 It should be noted that the sample sizes in the previous studies were small. Importantly, drugs that may alter SUA levels were not excluded from previous work as they were in this study.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…A real‐world experience with sofosbuvir‐based DAA regimens reported rash in up to 2.6% (n = 344) of patients: 6% with sofosbuvir, PEG‐IFN, plus ribavirin; 0% with sofosbuvir plus ribavirin; and 0% with sofosbuvir and daclatasvir/ledipasvir with or without ribavirin . Two other real‐world studies did not report any rash related to sofosbuvir‐based regimens . Interestingly, these studies failed to provide the morphologic description of the rash associated with the DAAs.…”
Section: Discussionmentioning
confidence: 99%
“…(7) Two other realworld studies did not report any rash related to sofosbuvir-based regimens. (8,9) Interestingly, these studies failed to provide the morphologic description of the rash associated with the DAAs. However, recently there have been reports of seborrheic dermatitis and erythema multiforme with the use of sofosbuvir and daclatasvir, (10,11) lichenoid eruptions with sofosbuvir and simeprevir, (12) and erythrodermic pityriasis rubra pilaris eruptions with sofosbuvir.…”
Section: Discussionmentioning
confidence: 99%